Synthesis of silver nanoparticles and their role against a thiazolekinase enzyme from Plasmodium falciparum - Yao, Jia (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Malaria, a mosquito-borne infectious disease, caused by the protozoan Plasmodium genus, is the greatest health challenges worldwide. The plasmodial vitamin B1 biosynthetic enzyme PfThzK diverges significantly, both structurally and functionally from its counterpart in higher eukaryotes, thereby making it particularly attractive as a biomedical target. In the present study, PfThzK was recombinantly produced as 6Ã—His fusion protein in E. coli BL21, purified using nickel affinity chromatography and size exclusion chromatography resulting in 1.03% yield and specific activity 0.28 U/mg. The enzyme was found to be a monomer with a molecular mass of 34 kDa. Characterization of the PfThzK showed an optimum temperature and pH of 37Â°C and 7.5 respectively, and it is relatively stable (tâ‚ /â‚‚=2.66 h). Ag nanoparticles were synthesized by NaBHâ‚„/tannic acid, and characterized by UV-vis spectroscopy and transmission electron microscopy. The morphologies of these Ag nanoparticles (in terms of size) synthesized by tannic acid appeared to be more controlled with the size of 7.06Â±2.41 nm, compared with those synthesized by NaBHâ‚„, with the sized of 12.9Â±4.21 nm. The purified PfThzK was challenged with Ag NPs synthesized by tannic acid, and the results suggested that they competitively inhibited PfThzK (89 %) at low concentrations (5-10 Î¼M) with a Ki = 6.45 Î¼M.
Keywords: Silver; Nanoparticles; Thiazoles; Plasmodium falciparum; Antimalarials; Malaria -- Chemotherapy